RETRACTED: Transforming Growth Factor-β1 Promotes M1 Alveolar Macrophage Polarization in Acute Lung Injury by Up-Regulating DNMT1 to Mediate the microRNA-124/PELI1/IRF5 Axis - Wang, Yongqi; Wang, Xiaoqing; Zhang, Hong; Han, Biao; Ye, Yuanmei; Zhang, Mengjie; Wang, Yingbin; Xue, Jianjun; Wang, Chun’ai (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Macrophages function as key orchestrators in the pathogenesis of acute lung injury (ALI). The current study set out to investigate the molecular mechanism of transforming growth factor-β (TGFβ1) in the regulation of M1 alveolar macrophage polarization in ALI by modulating DNA methyltransferase 1 (DNMT1), along with the microRNA (miR)-124/Pellino 1 (PELI1)/interferon regulatory factor 5 (IRF5) axis. Methods: First, ALI mouse models were established, and the proportion of M1 and M2 macrophages in mouse lung tissues was detected using flow cytometry. The targeting relationship between miR-124 and PELI1 was verified with the help of a dual luciferase gene reporter assay. Following TGFβ1 knockdown, RT-qPCR and Western blot assay were performed to analyze the expression patterns of TGFβ1, DNMT1, miR-124 and PELI1 and M1/M2 polarization markers in the lung tissues of ALI mice. Immunofluorescence was further employed to detect nuclear translocation of IRF5 in macrophages. Results: The polarization of M1 macrophages was found to be positively-correlated with the severity of lung injury. TGFβ1, DNMT1, PELI1 were highly-expressed, while miR-124 was down-regulated in ALI mice, and IRF5 was primarily distributed in the nucleus. TGFβ1 promoted the polarization of M1 alveolar macrophages by up-regulating DNMT1. Furthermore, DNMT1 down-regulated the expression of miR-124, which led to enhancement of M1 alveolar macrophage polarization. Meanwhile, over-expression of miR-124 inhibited the nuclear translocation of IRF5 and suppressed M1 alveolar macrophage polarization. On the other hand, over-expression of PELI1 reversed the above trends. Conclusion: Collectively, our findings indicated that TGFβ1 can promote the expression of DNMT1, which down-regulates miR-124 to activate PELI1 and nuclear translocation of IRF5, thereby aggravating ALI in mice.